Load reduction for two-bladed horizontal-axis tidal current turbines based on individual pitch control. (1st July 2020) - Liu, Hongwei; Li, Yangjian; Lin, Yonggang; Li, Wei; Gu, Yajing
Abstract: With the large progress in tidal current energy, the size of tidal current turbine (TCT) rotors has increased, leading to more substantial asymmetrical loads. In this study, severe asymmetrical loads were investigated by a sea trial experiment with a 600-kW two-bladed horizontal-axis TCT. Individual pitch control (IPC) has been recommended and validated to be effective for load reductions. Each blade is individually and actively controlled during IPC to compensate for asymmetrical loads within the rotational cycle. IPC has significant engineering implications but may cause partial energy loss under below-rated conditions. However, the conventional IPC method has limitations for two-bladed turbines. Thus, to alleviate the fatigue loads of two-bladed TCTs, a new IPC method based on vector analysis is presented in this paper. An integral sliding mode controller is designed for the proposed IPC to eliminate the phase lag resulting from the signal filter and actuator. To validate the feasibility and investigate the performance of the proposed sliding mode control (SMC) strategy, a collaborative simulation using GH-Bladed and Simulink was carried out. The comparative simulation results demonstrated the feasibility of the proposed IPC method and the better performance of the proposed SMC controller compared with a conventional PI controller. Highlights: Severe asymmetrical loads are investigated by a two-bladed 600-kW TCT experiment. A new IPC approach for two-bladed TCT is proposed based on vector analysis. An integral SMC controller with high feasibility is designed. A collaborative simulation is carried out for validation.